Paracrystalline WO3 additive-free monodisperse inks for large-scale electrochromic devices - Peng, Jian; Wang, Likun; Zhao, Gaoling; Tan, Ziyi; Shen, Lukai; Hao, Xiaoyue; Ma, Sainan; Liu, Yong; Han, Gaorong (Elsevier B.V., 2026)
Electrochromic smart windows are promising for building energy savings since they can dynamically regulate the sunlight spectrum. Herein, we report a previously unexplored paracrystalline WO3 electrochromic films featuring a unique amorphous-paracrystalline-crystalline homogeneous composite structure, which are controllably synthesized by a facile inkjet printing process that relies on additive-free monodisperse inks. The emergence of a paracrystalline phase facilitates enhanced ion transport and structural robustness, enabling electrochromic devices (ECDs) with dual-band tri-state modulation. The obtained ECDs demonstrate high optical contrast (56.12% at 633 nm, 50.33% at 1200 nm), fast response times (coloring/bleaching times of 2.4 s and 3.0 s), excellent coloration efficiency (159.7 cm2 C−1), and superior cycling stability (after 3000 cycles with 96.8% retention). The simulation reveals that the smart window achieves an energy savings of 58.75 MJ m−2 and a reduction of 9.31 kg of CO2 emissions per square meter of the building annually. This work provides mechanistic insights into paracrystalline formation in oxide films and validates a scalable ink-based strategy for fabricating high-performance flexible and large-scale electrochromic devices, paving the way for sustainable energy-saving technologies.